Zoning, density, and rising housing prices: A case study in Portland, Oregon. (December 2019) - Dong, Hongwei; Hansz, J Andy
This study uses path analysis models to evaluate the associations between zoning, development density and the sales prices of new and existing single-family homes at the dwelling-unit level in Portland, Oregon. Development density is associated with the sales prices of single-family homes directly by determining land costs and indirectly by correlating with the size and construction costs of structures. A prominent trend in Portland's and the nation's real estate markets is that new single-family homes are getting bigger. Another trend is that single-family homes have been built on smaller lots despite their growing floor areas. Because developers tend to build smaller homes on smaller lots, the decline of lot sizes helps to contain the effect of growing home size on housing prices. However, the counter effect of smaller lot sizes is somewhat weak because home sizes have a stronger association with housing prices than lot sizes. Homebuyers in Portland are willing to pay a premium to live in neighbourhoods with higher densities, which further limits the potential of higher density development as a tool to reduce single-family home costs. In addition to its indirect associations with home prices via the determination of lot and home sizes, zoning exhibits a significant and direct association with the prices of existing single-family homes, but not with the sales prices of new single-family homes. Existing single-family homes in higher density zones tend to sell at lower prices, ceteris paribus, suggesting that the concern of future neighbourhood change prevails over the opportunity for redevelopment.